"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Pas ce soir, chéri, j’ai mal à la tête (parce que je fais ton lavage) - Massicolli, Elisabeth (Gazette des femmes, 2022)
Quel est le lien entre la charge mentale et l’épanouissement sexuel des femmes au sein des couples hétérosexuels? On fait le point. Dans le livre Women Who Run With the Wolves, la psychanalyste Clarissa Pinkola Estés écrit : « Il y a cette drôle de chose à propos du nettoyage de la maison… c’est que c’est une tâche qui n’est jamais terminée. C’est la façon parfaite d’empêcher une femme de faire quoi que ce soit d’autre. » L’autrice parle ici du processus créatif : elle affirme que l’art ne peut pas être pratiqué que dans des moments « volés », entre une brassée de lavage et la préparation du souper. Que l’art prend du temps et que l’artiste doit agir avec ses pulsions et, pour y arriver, être en mesure de se reposer.
Keywords: 2000 à aujourd'hui; approches et analyses; charge mentale; conciliation famille-travail; famille; hétérosexisme; projet charge mentale; périodes historiques; ressource en ligne; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; travail domestique

Homoparentalités, état des lieux - Gross, Martine; Association des parents et futurs parents gays et lesbiens; Colloque Parentés et différence des sexes (Érès, 2005)
«Bourdieu avait déjà considéré que la famille, loin d'être une "donnée immédiate de la réalité sociale" était en fait "un instrument de construction de cette réalité". Quelle signification donner alors au présent ouvrage consacré aux familles homoparentales ? Il y a dans cet intitulé l'expression d'une revendication qui a pris toute sa force au cours des dernières décennies : celle de pouvoir être parent et homosexuel, cette revendication étant indissociable de l'aspiration à constituer une famille comme les autres. C'est bien dans ce mouvement que s'inscrit cet ouvrage, militant au meilleur sens du terme. L'objectif est en effet l'existence dans l'espace public d'un fait social dans toute sa complexité, c'est-à-dire avec la volonté d'un traitement raisonnable (au sens de faire appel à la raison) fondé sur un recours intensif aux sciences de l'homme.Distinguer la procréation de la sexualité et considérer que le couple conjugal et parental peut ne pas être fondé sur la différence des sexes, ceci tout en revendiquant le droit au label "famille", c'est consacrer le fait que la famille ne s'impose plus aux individus comme une institution immuable à laquelle il n'ont comme choix que celui de s'ajuster ; ils se donnent désormais le droit de concevoir l'organisation de leur univers privé en fonction de leurs propres aspirations et en référence à des valeurs qui prétendent relever tout autant de l'intérêt général que de celui des enfants éventuellement concernés.» Jacques CommailleRendant compte des études théoriques sur la parenté et des recherches sociologiques, ethnologiques, anthropologiques, juridiques et cliniques sur les familles homoparentales et leurs enfants, cette nouvelle édition, revue, mise à jour et augmentée, constitue une référence incontournable pour aborder les interrogations suscitées aujourd'hui par la très controversée question de l'homoparentalité.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; famille; france; hétérosexisme; identités LGBTQIA2+; maternité; parentalité; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Les familles homosexuelles aux États-Unis : dissolution d'un mouvement social ou redéfinition de sa portée politique? - Marche, Guillaume (Revue française d'études américaines, 2003)
Families are a challenge to the lesbian and gay movement in the United States, since homosexuality is largely construed as antithetical to "the family". By creating a wide variety of alternative families gays and lesbians however articulate an identity claim which may not be framed exclusively either in terms of assimilationism, or of differentialism. For this reason these alternative families present American society with a transformative potential which is in a position to exert its influence beyond the bounds of the gay and lesbian community. Far from being a hindrance in terms of efficiency, the very fact that these families constitute a private locus of gay and lesbian experience furthermore contributes to the lesbian and gay movement's expressive dimension, which is of crucial strategic importance in contemporary American society.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; famille; familles homoparentales; his4443; homoparentalité; hétérosexisme; identités LGBTQIA2+; lesbianisme; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; parentalité; patriarcat; philosophie politique; premier cycle; queer; régions géographiques; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques; états-unis; études américaines

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Columbia University Press, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Section: xxii, 156 p. ; 24 cm.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis